SLC37A4‐CDG: Second patient - Matthew P. Wilson (JIMD Reports, 2021)
Abstract Recently, a disorder caused by the heterozygous de novo c.1267C>T (p.R423*) substitution in SLC37A4 has been described. This causes mislocalization of the glucose‐6‐phosphate transporter to the Golgi leading to a congenital disorder of glycosylation type II (SLC37A4‐CDG). Only one patient has been reported showing liver disease that improved with age and mild dysmorphism. Here we report the second patient with a type II CDG caused by the same heterozygous de novo c.1267C>T (p.R423*) mutation thereby confirming the pathogenicity of this variant and expanding the clinical picture with type 1 diabetes, severe scoliosis, and membranoproliferative glomerulonephritis. Additional clinical and biochemical data provide further insight into the mechanism and prognosis of SLC37A4‐CDG.